1991
DOI: 10.1007/bf00232331
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency plant regeneration from cotyledons of watermelon (Citrullus vulgaris Schrad)

Abstract: Cotyledons of various ages from seedlings of eight watermelon (Citrullus vulgaris) cultivars were cultured on MS medium supplemented with different combinations of phytohormones. High frequency shoot regeneration (60.0-92.0%) was induced from 5-day-old cotyledons of cultivars cultured on MS medium containing 5.0 mg/l 6-benzylaminopurine (BA) and 0.5 mg/l indole-3-acetic acid (IAA). Multiple shoot buds elongated on MS medium containing 0.2 mg/l kinetin (KT) and 5-10 shoots per expiant could be recovered dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
6
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 12 publications
3
43
6
3
Order By: Relevance
“…Young explants have been shown to give better results than older explants in most Brassica species (Chakrabarty et al 2002;Sharma et al 2012;Sharma et al 2014). Dong and Jia (1991) have reported that shoot differentiation frequencies of cotyledonary explants from seedlings older than 7 days dropped sharply. A possible explanation is that young cotyledon and hypocotyl explants are physiologically and biochemically more active as they have less rigid cell wall and are easily affected by the environmental factors such as exogenous plant growth regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Young explants have been shown to give better results than older explants in most Brassica species (Chakrabarty et al 2002;Sharma et al 2012;Sharma et al 2014). Dong and Jia (1991) have reported that shoot differentiation frequencies of cotyledonary explants from seedlings older than 7 days dropped sharply. A possible explanation is that young cotyledon and hypocotyl explants are physiologically and biochemically more active as they have less rigid cell wall and are easily affected by the environmental factors such as exogenous plant growth regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Seedling age is reported to be an important factor for obtaining high frequency adventitious shoot regeneration in watermelon (Choi et al, 1994;Compton & Gray, 1994). For watermelon organogenesis, explants were collected from seedlings younger than five-dayold (Choi et al, 1994;Compton, 2000), as young cotyledons are physiologically very active and respond efficiently to exogenous hormones (Dong & Jia, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The composition of induction media is also important for adventitious bud development; the presence of cytokinin is critical for shoot induction and for differentiation from cotyledonary explants of watermelon (Dong & Jia, 1991). BAP has been reported as highly Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations